2006
DOI: 10.1002/elps.200500813
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of whole‐genome amplification of low‐copy‐number DNA in chimerism analysis after allogeneic stem cell transplantation using STR marker typing

Abstract: Whole-genome DNA amplification (WGA) is a promising method that generates large amounts of DNA from samples of limited quantity. We investigated the accuracy of a multiplex PCR approach to WGA over STR loci. The amplification bias within a locus and over all analyzed loci was investigated in relation to the amount of template in the WGA reaction, the specific STR locus, and allele length. We observed reproducible error-free STR profiles with 10 ng down to 1 ng of DNA template. The amplification deviation at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…WGA could be used as a tool for enriching DNA from clinical samples with limited cell populations as seen in pancytopenic patients such as leukemia, aplastic anemia, and splenomegaly. Nagy and colleagues 15 recently showed that WGA was useful for single‐tandem repeats profiling for chimerism analysis after allogeneic hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…WGA could be used as a tool for enriching DNA from clinical samples with limited cell populations as seen in pancytopenic patients such as leukemia, aplastic anemia, and splenomegaly. Nagy and colleagues 15 recently showed that WGA was useful for single‐tandem repeats profiling for chimerism analysis after allogeneic hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results are based on the utility of DNA generated by MDA from as low as 2.5 ng of template DNA; however, earlier reports have shown that DNA generated by MDA from very low amount of template DNA (e.g. 100 or 10 pgm) are not very good for tests such as STR genotyping (13).…”
Section: Introductionmentioning
confidence: 89%
“…The deviation does not appear to be due to a specific amplification bias as both higher and lower mixed chimerism percentages were observed with MDA-generated DNA when compared with native biological DNA. Earlier, Nagy et al (13) have also showed that mixed chimerism percentage varies between WGA and native biological DNA specimens. One alternative approach could be the use of pooled DNA from multiple WGA reactions for the same sample, although we have not tested this possibility in our study.…”
Section: Introductionmentioning
confidence: 91%
“…Whole-genome amplification (WGA) may overcome the challenge of low DNA concentration, since reliable amplification of forensic markers by WGA has resulted from as little as 1 ng of input DNA. Increased WGA error rates with smaller amounts of input DNA may be offset with pooled WGA samples [39].…”
Section: Strategies To Overcome Poor Sample Quality and Quantity Befomentioning
confidence: 99%